"Sakaratul Maut" Karya 'Abd al-Ra'ūf al-Fanṣūrī : Teks Dan Doktrin Sakratulmaut Di Jawi Abad XVII-XVIII - Tarobin, Muhammad (Jurnal Lektur Keagamaan, 2020)
Sakaratul Maut is a Malay translation of Lubb al-Kasyf wa al-Bayān limā yarāhu al-Muḥtaḍar bi al-'Iyān  manuscript by 'Abd al-Ra'ūf ibn 'Alī al-Jāwī al-Fanṣūrī  (d. 1693 AD). A study of this manuscript is important to identify the sakratulmaut doctrine that developed in Jawi in the XVII-XVIII centuries. This study aims to: first, make comparisons of several copies of the Sakaratul Maut manuscripts with the Sakrat al-Maut manuscript collected in Nagara, South Kalimantan which is claimed to be the work of 'Abd al-Ra'ūf ibn 'Alī al-Jāwī al-Fanṣūrī . This was done because contents of the last manuscript was presumed to be different from the existing manuscripts. Second, to identify the sakratulmaut doctrine that developed in the Jawi. Based on the philological approaches, this study finds that: first, based on the study of text structure it is known that the Sakrat al-Maut text in the Nagara collection have many differents content structures from the Sakaratul Maut text by al-Fanṣūrī. Second, a comparative analysis with texts that have existed before and after Sakaratul Maut found that sakratulÂmaut doctrines in Jawi was conveyed with a narrative classifications of the four and five patterns, namely by connecting four or five colors as representations of creatures accompanied by four or five kinds recitation of zikir. Keywords: Philology; Jawi; Neo-Sufism; Sakratulmaut; Traditional Sakaratul Mautmerupakan naskah terjemahan Melayu dari naskah Lubb al-Kasyf wa al-Bayān limā yarāhu al-Muḥtaḍar bi al-‘Iyān karya‘Abd al-Ra’ūf ibn ‘Alī al-Jāwī al-Fanṣūrī (w. 1693 M). Kajian terhadap naskah ini penting untuk melakukan identifikasi terhadap doktrin sakratulmaut yang berkembang di Jawi pada abad XVII-XVIII. Tulisan ini bertujuan untuk: pertama, melakukan perbandingan atas beberapa salinan naskah Sakaratul Mautdengan naskah Sakrat al-Mautkoleksi Nagara, Kalimantan Selatan yang diklaim sebagai karya ‘Abd al-Ra’ūf al-Fanṣūrī. Hal ini dilakukan karena isi naskah terakhir diduga berbeda dengan naskah-naskah yang telah ada. Kedua, untuk melakukan identifikasi terhadap ajaran sakratulmaut yang berkembang di Jawi. Berdasarkan pendekatan filologi, studi ini menemukan bahwa: pertama, berdasarkan kajian strukturteks diketahui bahwa naskah Sakrat al-Mautkoleksi Nagara memiliki struktur isi yang berbeda dengan naskah Sakaratul Maut karya al-Fanṣūrī. Kedua, analisis perbandingan dengan teks-teks yang telah ada sebelum dan sesudah Sakaratul Maut menemukan bahwa doktrin sakratulmaut di Jawi disampaikan melalui narasi klasifikasi pola empat dan lima, yakni dengan menghubungkan empat ataulima warna sebagai representasi makhluk disertai dengan empat atau lima macam bacaan zikir. Kata Kunci: Filologi; Jawi, Neo-Sufisme; Sakratulmaut; Tradisional.